Diferentes leituras do passado no monumento aos bandeirantes em Santana de Parnaíba/SP: ensino de história e memória social - Caetano, Janaina Franzoni [UNIFESP] (2020)
This work proposes the use of the monument in History Teaching, as a documentary source, which contributes to the knowledge of the past. The central objectives are: a) Analyze the monument in its different temporalities and functions, starting from the conception that it is an object intentionally created and used by a certain group to perpetuate a memory; b) Reflect the relationship between the construction of social memory and the monument; c) To understand how the Teaching of History can help in the critical reading and the deconstruction of the memory preserved in the monument, to understand how this object is constituted of different narratives of the past. Through the study of the Bandeirantes Monument located in the city of Santana de Parnaíba, SP, one seeks to understand how it is possible to study the historical processes and the construction of the social memory of a city through this object. At the end, as a propositive part arising from the research process, we present a didactic sequence that indicates to the teacher activities to think about the monument historically, in order to deconstruct its narrative, understand which reading of the past it invokes and analyze the relationship between memory and intrinsic forgetfulness in its form. For this purpose, guidelines are suggested to use the monument as a document, regardless of the city where it is located.